الصناديق الوقفية الكويتية وأهميتها في تنمية التعليم - قريشة, نجاة; عبيد, حياة (جامعة الوادي - University of Eloued, 2022)
لعب الوقف دوراً مهماً في حياة المسلمين وبخاصة فيما يتعلق بالتعليم على مر العصور، وبعد التقدم الحضاري الذي أثر في القطاعات كان لزاما على قطاع الأوقاف مواكبة هذه العصرنة وإيجاد صيغ تمويلية حديثة أكثر تطوراً، فظهر بما يسمى الصناديق الوقفية التي لقيت انتشاراً واسعاً حققت من خلاله الريادة، وتعتبر الكويت من الدول الرائدة في هذا المجال، انطلاقاً من فلسفتها في إحياء هذه المفاهيم الحضارية والتنموية، التي تهدف في الجملة إلى إحياء سنّة الوقف، وتطوير العمل الخيري، وتلبية حاجيات المجتمع في المجالات غير المدعومة كالتعليم، وتحقيق المشاركة الشعبية وإعطاء الفرصة لجميع الأفراد, وتجديد الدور التنموي للوقف التعليمي وفوائده المتعددة من خلال صندوق الوقف التعليمي. The endowment had played significant role in Muslim's life, especially in relationship to education, throughout different historical ages the civilized progress affected the sectors, it was necessary for the endowment sector to keep pace with this modernization and to find more advanced modern financing formulas in the other side. The endowment funds have been appeared which gained wide spread through the means that achieved leadership, therefore Kuwait as considered one of the leading countries in this field, based on its philosophy of reviving These civilized and development concepts, which aim in general to revive the Sunnah of the endowment, develop charitable work, meet the needs of society in unsupported fields such as education, achieve popular participation and give opportunity to all individuals, and renew the developmental role of the educational endowment and its multiple benefits through the Educational Endowment Fund.
Kuwaiti Endowment Funds and their Importance in the Development of Education
مقال
Keywords: الوقف ; الصناديق الوقفية ; التعليم ; الكويت; endowment; endowment funds; education; Kuwait.